Pelatihan Pengamatan Morfologi Bakteri Bagi Siswa Kelas X di SMA Negeri 1 Parigi Tengah - Slamet Ifandi; Astri Febriana Iffaf; Hermin Lastri Gintoe (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This bacterial morphology observation training was conducted for grade X students at SMA Negeri 1 Parigi Tengah. The main problem faced was the lack of knowledge and skills of students in the field of microbiology, especially in identifying bacterial morphology. The purpose of this activity was to improve students' understanding of basic biological concepts and practical skills in bacterial observation. The methods used included delivering material on the principles and techniques of bacterial morphological characterization, as well as direct practice using microscopes and Gram staining techniques. The results showed that students successfully identified Staphylococcus aureus bacteria in the form of cocci with Gram positive and Bacillus sp. in the form of bacilli with Gram negative. This activity has proven effective in improving students' understanding and skills in microbiology, as well as encouraging their interest in studying biology further